Development of SISTANA-based LKPD to enhance understanding of volcanic disaster mitigation at elementary schools - Misbahuddin, Hajir; Aditia Wiguna, Frans (Universitas Nusantara PGRI Kediri, 2023)
The limitation of students' understanding of disaster mitigation led the researchers to conduct a study that combined two previous studies, resulting in a new finding called Sistana. This research aimed to describe the suitability, effectiveness, and student response to the learning media in the form of Sistana-Based Student Worksheets (LKPD) in enhancing their understanding of disaster mitigation during the 6th-grade Social Studies class in Elementary School. The development model utilized by the researchers was the 4D model, which consists of four main stages: define, design, develop, and disseminate. The validation results by material experts showed a percentage of 80% as